Math word problems demystified - Bluman, Allan G. (Unites States of America : McGraw Hill Education, 2005)
All mathematics books have problems, and most of them word problems. Many students have difficulties when attempting to solve word problems. One reason is that they do not have any specific plan of action.
Lesson1. Introduction to solving word problem -- Lesson2. Solving word problems using whole number -- Lesson3. Solving word problems using decimal -- Lesson4. Solving word problems using decimal -- Lesson5. Solving word problems using percents -- Lesson6. Solving word problem using proportions -- Lesson7. Solving word problem using formulas -- Lesson8. Algebraic representation -- Lesson9. Solving number problems -- Lesson10. Solving digit problems -- Lesson11. Solving coin problems -- Lesson12. Solving age problems -- Lesson13. Solving distance problems -- Lesson14. Solving mixture problems -- Lesson15. Solving finance problems -- Lesson16. Solving lever problems -- Lesson17. Solving work problems -- Lesson18. Solving word problems using two equations -- Lesson19. Solving word problems using quadratic equations -- Lesson20. Solving word problems in geometry quiz 5 -- Lesson21. Solving word problems using other strategies -- Lesson22. Solving word problems in probability -- Lesson23. Solving word problems in statistics .
Includes index.
Keywords: MATHEMATICS